Treatment of spasticity in patients with the consequences of traumatic brain injury - A. P. Kovalenko; I. A. Vozniuk; K. M. Naumov; V. Yu. Lobzin; S. Yu. Kirtaev (Неврология, нейропсихиатрия, психосоматика, 2022)
Up to 16–20% of patients with a history of traumatic brain injury (TBI), regardless of its severity, suffer from pronounced spasticity, cognitive, vestibular and motor disorders. At the same time, data on the effectiveness of botulinum neurotoxin (BoNT) in the treatment of post-traumatic spasticity is lacking.Objective: to assess the effectiveness of peripheral myorelaxants (botulinum neurotoxin type A) in the treatment of past-traumatic spasticity.Patients and methods. 21 male patients aged 25 to 48 years with post-traumatic spastic hemiparesis (at least 6 months after the injury) were examined. 450 to 850 U (mean – 650 U) of BoNT (incobotulinumtoxin) was injected into the spastic muscles of the upper and lower extremities. The follow-up assessment of spasticity and paresis was performed 24±3 days after BoNT injection. Patterns of spasticity were studied: shoulder adduction, elbow joint flexion, forearm pronation, hand and finger flexion, hip adduction, shin flexion, foot flexion, toe flexion. The following methods were used: original methods of manual testing (MMT) of spasticity, Tardieu scale (TS), modified Ashworth scale (MAS), Medical Research Council Scale (MRCS) to assess paresis.Results and discussion. 24±3 days after incobotulotoxin administration, we observed a significant 1.5–2-fold decrease in spasticity angle (xS) and a reduction in the angle of neuromuscular reactivity (xV3) by 15–30° in all the studied patterns. Changes of xV1 (muscle extensibility) and xA (muscle strength) were not significant. No adverse reactions were observed. The use of MMT and TS has shown its effectiveness and specificity in the evaluation of spasticity and effectiveness of BoNT, and in the dynamics of muscle condition.Conclusion. The study showed the feasibility of using MMT and TS in the evaluation and assessment of spasticity, as well as the effectiveness and safety of incobotulinumtoxin (Xeomin) in dosages from 450 to 850 U in the treatment of spasticity of the upper and lower extremities in patients with the consequences of TBI.